Efektivitas Sistem Informasi Kesejahteraan Sosial Next Generation di Kelurahan Gunung Seteleng Menggunakan Framework TAM - Fatma Wati; Joy Nashar Utamajaya; Aditya Pratama (JURIKOM (Jurnal Riset Komputer), 2022)
The Next Generation Social Welfare Information System (SIKS-NG) is a management application for the process of improving and proposing a new Integrated Database (BDT) in which there is also a module for improving and proposing non-PKH Food Social Assistance (BSP) data in the Gunung Seteleng village.This study aims to measure the effectiveness of the SIKS-NG information system in the Gunung Seteleng village whether the use of the information system has been running effectively or not. The research model used is the Technology Acceptance Model (TAM) with 4 constructs.From the measurement results, it is found that the PEOU variable (ease of use) with a percentage value of 68.33% is included in the Effective category, the PU variable (perception of usability) with a percentage value of 67.74% is included in the Effective category, the ATU variable (use attitude) with a value of 67.74%. the percentage of 66.81% is included in the effective category, and the ACC variable (use satisfaction) with a percentage value of 68.22% is included in the effective category, so it can be concluded that the overall research results of each variable measuring the effectiveness of the SIKS-NG information system in the Gunung Seteleng village are in the Effective category